THE INFLUENCE OF INSTRUCTIONAL VIDEOS WITH THE CAPTION OF MAKING HASTA WORKS FROM BANANA TREE FRIENDS ON INCREASING THE KNOWLEDGE OF CLASS 8 STUDENTS OF SMPN 1 PAMIJAHAN - Setyan, Sulis; Muslikhah, Febri palupi; Rijalul Fikri, Luthfy (Fakultas Ilmu Dakwah dan Komunikasi, 2022)
Knowledge and student learning abilities, especially for skills, require a learning that can attract students' attention and increase student motivation during the teaching and learning process including when learning skills, one of the media that can be used is instructional video learning media. The purpose of this study was to determine the effect of captions in instructional videos on increasing student knowledge and to analyze the effect of captions in instructional videos by banana tree stalks on increasing knowledge of 8th grade students of SMP Negeri 1 Pamijahan. This research uses quantitative methods. This type of research used in this research is a quasi experimental research design and the instrument used in this study is a test. In this study, 2 data analysis tests were conducted, namely the prerequisite analysis test and hypothesis testing. The prerequisite analysis test was to test the normality and homogeneity between the experimental group and the control group subject and then to test the hypothesis between the experimental group and the control group. Based on the data analysis, the results of this study are that there is an effect of instructional videos with the caption of making hasta by banana tree stalks on increasing the knowledge of grade 8 students of SMPN 1 Pamijahan. This is evidenced by testing using paired sample t test with sig results. (2-tailed) 0.000 with a level of α 0.05, the Sig value is smaller than alpha, so there is a significant difference between the increase in knowledge of pretest and posttest instructional video data with captions.